Like in love with you : a novel - Alban, Emma R. (Avon, an imprint of HarperCollins Publishers, 2026)
When Catherine Pine relocates to Bath in 1817, she comes face-to-face with her mother's arch nemesis and her daughter - the wildly popular Lady Rosalie. Twenty-five years after a horrible betrayal, Catherine's mother sees the perfect opportunity for revenge: Catherine must win the favour of Lady Rosalie's suitor and unofficial betrothed, the most eligible Mr Dean. Only Catherine soon discovers that Lady Rosalie is by far the wittiest, cleverest, most intriguing young woman Catherine's ever met, and she's instantly smitten. Which is a problem. Meanwhile, Lady Rosalie feels trapped in her relationship with Mr Dean and in her role as Bath's resident mean girl. But when she notices newcomer Catherine gunning for her spot as queen bee, Rosalie finally feels a spark again - something she absolutely doesn't want to extinguish.